2020
DOI: 10.1088/1755-1315/481/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Shale structure implication in hydraulic fracturing production results: Case study in low resistivity low quality reservoir, offshore North West Java area

Abstract: Low-resistivity & low-quality reservoir has been successfully developed in ONWJ area by using hydraulic fracturing stimulation method to optimize production gain due to low-permeability reservoir property. The purpose of this research is to understand implication of shale structure for increasing gain production after hydraulic fracturing stimulation. Implementation of hydraulic fracturing was first completed at BerylE-1 and the well could produce 455 BOPD at 560 psi in reservoir 33 and 35. This reservoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Among these factors, the mineral fraction content plays a key role in determining the properties of a shale reservoir and the hydraulic fracture extension. Kusuma et al 29 and Ferguson et al 30 observed production anomalies after hydraulic fracture stimulations, and the clay release caused by hydraulic fracturing increased the effective porosity and permeability. Vahab et al 31 and Taleghani et al 32 used numerical simulations to study the evolution of hydraulically driven fractures in naturally layered and fractured media.…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, the mineral fraction content plays a key role in determining the properties of a shale reservoir and the hydraulic fracture extension. Kusuma et al 29 and Ferguson et al 30 observed production anomalies after hydraulic fracture stimulations, and the clay release caused by hydraulic fracturing increased the effective porosity and permeability. Vahab et al 31 and Taleghani et al 32 used numerical simulations to study the evolution of hydraulically driven fractures in naturally layered and fractured media.…”
Section: Introductionmentioning
confidence: 99%